The Investigation of Peculiarities of the Occurrence of Subjective Civil Rights in Registration of a Patent - IASECHKO, Svitlana; PUZYRNYI, Viacheslav; PUZУRNA, Natalia; KOSTIUK, Nataliia; BAKHNOVSKA, Iryna; LITVINOVA, Iryna (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).17, 2020)
The main aspects of the impact of patents on technological and social development have been highlighted, and it has been suggested to adapt a powerful world experience in this field. The key aspects of the innovation process and the protection of the results of scientific and technical action with the help of patents, and the peculiarities of the occurrence of subjective civil rights are considered. The authors of the paper analyze the current legislative provisions and determine the direction of its development in the context of globalization. The article explores the theoretical construct of these relations and provides an analysis of civil legislation as applied to industry standards of economic legislation. The practical significance of the study is determined by the fact that the application of the developed provisions will facilitate the harmonization of national legislations in the formation of legal systems. The aim of the article is to supplement and clarify the ideas about patent and of subjective civil rights. The factors that influenced the development of the doctrine civil rights have been considered, in particular, taking into account the experience of European countries.